Corneal maps and anterior segment tomography of young mixed breed cats - Ramos, Leticia de Andrade [UNESP] (2025)
This research described corneal maps and anterior-segment tomographic images of young mixed breed cats and compared them to those described in humans. The exams of 13 mixed-breed cats (25 eyes) aged between 18 and 48 months were analyzed. The following maps provided by the Galilei G4 were analyzed qualitatively: axial and instantaneous curvature, pachymetry, total corneal power and best fit sphere (BFS) and best fit toric asphere (BFTA) elevation. Furthermore, anterior and posterior axial and instantaneous curvatures, total corneal power and pachymetry values were analyzed in addition to anterior segment tomography images. The topography maps described the central region of the cats’ cornea. Anterior and posterior axial curvature maps were uniformly flat. Instantaneous anterior curvature map was aspheric. A ring in a shape similar to a donut was observed in the posterior instantaneous curvature map. No patterns were observed in the elevation maps. Total corneal power maps tended to monofocality and eleven maps presented a regressive multifocal triangle in the inferior region. The pachymetry map was uniform and pachymetry among the corneal zones did not differ statistically. The anterior chamber was deep with a wide angle that narrows close to the periphery; the anterior and posterior corneal surfaces and the anterior surface of the lens tended to be parallel. Young mixed breed cats’ corneal maps and anterior segment tomographic images differed from those described in humans. The center of the cat’s cornea was flatter, spherical, uniformly thick and tended to monofocality. Anterior and posterior corneal surfaces and the anterior surface of the lens tended to be parallel.